The GW/BSE Method in Magnetic Fields - Holzer, Christof; Pausch, Ansgar; Klopper, Wim (Frontiers in Chemistry, 2021)
The GW approximation and the Bethe-Salpeter equation (BSE) have been implemented into the Turbomole program package for computations of molecular systems in a strong, ﬁnite magnetic ﬁeld. Complex-valued London orbitals are used as ba-sis functions to ensure gauge-invariant computational results. The implementation has been benchmarked against triplet excitation energies of 36 small to medium-sized molecules against reference values obtained at the approximate coupled-cluster level (CC2 approximation). Finally, a spectacular change of colour from red to green of the tetracene molecule is induced by applying magnetic ﬁelds between 0 and 10,000 tesla perpendicular to the molecular plane.